I'm not done with you yet - Sutanto, Jesse Q. (Berkley, 2023)
"A new, twisted suspense novel by national bestselling author Jesse Q. Sutanto. Jane is unhappy. A struggling midlist writer whose novels barely command four figures, she feels trapped in an underwhelming marriage, just scraping by to pay a crippling Bay Area mortgage for a house-a life-she's never really wanted. There's only ever been one person she cared about, one person who truly understood her: Thalia. Jane's best and only friend nearly a decade ago during their Creative Writing days at Oxford. It was the only good year of Jane's life-cobblestones and books and damp English air, heady wine and sweet cider and Thalia, endless Thalia. But then one night ruined everything. The blood-soaked night that should have bound Thalia to Jane forever but instead made her lose her completely. Thalia disappeared without a trace, and Jane has been unable to find her since. Until now. Because there she is, her name at the top of the New York Times bestseller list: A Most Pleasant Death by Thalia Ashcroft. When she discovers a post from Thalia on her website about attending a book convention in New York City in a week-"Can't wait to see you there!"-Jane can't wait either. She'll go to New York City, too, credit card bill be damned. And this time, she will do things right. Jane won't lose Thalia again"--